Alveolar epithelial cells in bacterial sepsis-associated acute lung injury: mechanisms and therapeutic strategies - Jia, Guiyang; Song, Erqin; Zheng, Zhiyou; Qian, Mingjiang; Liu, Guoyue (Frontiers in Immunology, 2025)
Bacterial Sepsis-Associated acute lung injury (ALI) and its progression to acute respiratory distress syndrome (ARDS) are clinically prevalent critical conditions with high morbidity and mortality. As a vital component of lung tissue, alveolar epithelial cells (AECs) play a crucial role in maintaining pulmonary homeostasis and are deeply involved in the pathophysiological processes of bacterial Sepsis-Associated ALI. This review systematically summarizes the pathophysiological changes in AECs during bacterial sepsis, focusing on oxidative stress, programmed cell death, and disruption of the epithelial barrier. It further explores the inflammatory responses triggered by both Gram-positive and Gram-negative bacteria, as well as the interactions between AECs and immune cells, shedding light on how these processes contribute to the inflammatory response during bacterial sepsis. It elaborates on the regulatory mechanisms of key molecular pathways, including Nuclear factor kappa-B (NF-κB), Nuclear Factor Erythroid 2-related Factor 2 (NRF2), nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 (NLRP3), and Toll-like receptor (TLR), in AEC dysfunction and inflammatory responses. Furthermore, therapeutic strategies for AEC injury are comprehensively analyzed from multiple perspectives, such as AEC repair and regeneration, modulation of inflammatory responses, restoration of barrier function, and exosome-based therapies. Although these approaches show promising results in preclinical studies, their clinical translation faces significant challenges. This review underscores the need for further research into the complex mechanisms of AEC injury in bacterial sepsis and advocates for the development of more targeted interventions to improve patient outcomes.